THE SYNDROME OF VASCULAR AGING AND ATHEROSCLEROSIS IN PATIENT OF HYPERTENSION II DEGREE - Галюк, Н. М. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Pulse, 2019)
Analysis of clinical and functional characteristics of hypertension second degree was determined based on survey 125 patients with hypertension who were treated in the Ivano-Frankovsk regional clinical cardiology clinic. We studied the peculiarities of hypertension in patients with ≤ 3-year history of antihypertensive therapy (60) and in patients with ≥ 5-year history of the same treatment (65 people). Long-term antihypertensive therapy, but the ability to control hypertension, can cause negative effects, which are based is worsening elastic-elastic properties of arteries and blood lipid spectrum.